An exploratory case study of Olympiad students’ attitudes towards and passion for science - Oliver, Mary; Venville, Grady (Taylor & Francis Group, 2011)
Much is known about high school students’ attitudes towards science but there is almost no research on what passion for science might look like and how it might be manifested. This exploratory case study took advantage of a unique group of highly gifted science students participating in the Australian Science Olympiad (n=69) to explore their attitudes towards school science and science as presented in the Olympiad summer camp. In particular the role the summer camp might play in igniting the students’ passion for science was a focus of the research. Data were collected through a two tiered survey of students’ attitudes towards school science, an evaluative survey of the Olympiad summer camp and in-depth interviews with six participants. Findings indicated that Olympiad students generally had positive attitudes towards school science with most selecting science as one of their favourite subjects. However, an underlying ambivalence about school science was noted in the data. In contrast, the Olympiad summer camp transformed students’ positive attitudes into passion for science. Seven themes emerged from the data providing a foundation for a model of what academic passion for science looks like.